Perbandingan Hasil Diagnosis Laboratorium pada COVID-19 menggunakan Metode Real Time-Polymerase Chain Reaction (RT-PCR) dan Metode Rapid Test Antigen - Rahmadhaniati Rahmadhaniati (Jurnal Kesehatan, 2022)
Background: The 2019 Coronavirus Outbreak (COVID-19) is a global health emergency. Several methods are used to diagnose COVID-19, including the RT-PCR and the Rapid Antigen Test. Purpose: The aim of this analysis is to compare the sensitivity and specificity of the RT-PCR and the Rapid Antigen Test methods. Method : The information for this study came from three sources (Pubmed, Science Direct, and Google Scholar), and a literature search was conducted in October 2020. MeSH and a checklist prism were used to see if the analysis was feasible (title, abstract, and full text). The data is tabulated and a narrative analysis is used to present the information. Twelve studies met the inclusion criteria as a result of this study. The existing study is divided into two parts based on the theme: sensitivity, specificity of the RT-PCR method and the sensitivity, specificity of the antigen rapid test method(n=10) and the sensitivity, specificity of the antigen rapid test method(n=2). Sex, symptoms, Ct value determination, sensitivity values, and logistical constraints are some of the factors that influence the analysis of the RT-PCR process. Meanwhile, the type of sample, the officer who takes the swab, the duration of exposure, the virus material, and other confounding factors all affect the rapid test antigen method's review. Result : The sensitivity values for the Rapid Antigen Test using RT-PCR were 50.5% -100% and 11.7%-93.9%. The Rapid Antigen Test by RT-PCR has a specificity of 98.4%-100% and a 92%-100%. Conclusion: The RT-PCR is superior to the Rapid Antigen Test in terms of sensitivity and specificity.